Zeros Distribution of the Jones Polynomial for Pretzel Links (Communications in Mathematical Research, 2021)
In this paper, we deal with basic properties of some pretzel links andproperties of the Jones polynomials of some pretzel links. By using these properties,the zero distribution of pretzel links is studied. We discuss the properties of the Jonespolynomial of non-tame pretzel links and give that zeros of the Jones polynomial ofthese pretzel links are distributed on the planar curves.
Keywords: Jones polynomial; zero; pretzel link.